Evaluating the impact of rock climbing on mental health and emotional well-being in adolescents - Gürer, Hüseyin; Akçınar, Faruk; Arslan, Semiha Cömertoğlu; Akçınar, Serpil; Güllü, Mehmet; Eken, Özgür; Kurtoğlu, Ahmet; Ilkım, Mehmet; Alotaibi, Madawi H.; Elkholi, Safaa M. (Frontiers in Psychology, 2024)
Background: Rock climbing (RC) has gained attention as a therapeutic tool in psychiatric settings that merges physical exertion with mental engagement. It has potential to enhance mental health, through improved self-efficacy and social interaction, making it a novel intervention for addressing anxiety, depression, and behavioral issues in adolescents. This study aimed to investigate the effects of RC as a physical activity on anxiety, depression, and emotional and behavioral problems in adolescents.The current study included 57 athletes aged 14.5±1.7 years and 91 adolescents aged 13.6±1.2 years, matched for age and gender, who were not professionally involved in sport. In addition to the socio-demographic form, a detailed psychiatric assessment was carried out by the child psychiatrist; using the Schedule for Affective Disorders and Schizophrenia for School-Age Children Present and Lifetime Version (K-SADS-PL) to detect psychiatric conditions. The Revised Child Anxiety and Depression Scale-Child Version (RCADS-CV) and the Strengths and Difficulties Questionnaire (SDQ) were also administered to the adolescents in the study. Results: In the comparative analysis of the RCADS-CV outcomes between the athlete and control groups, the athletes demonstrated notably lower scores for both Separation Anxiety Disorder (SAD) and Generalized Anxiety Disorder (GAD), yielding p-values of <0.001 and 0.031, respectively. Although the mean scores for social phobia, OCD, panic disorder, and MDD were lower in the athlete group, the differences were not statistically significant (p > 0.05). In the correlation analysis, a moderately significant correlation was found between the duration of doing sport and the scale scores for SAD (p:0.010), OCD (p:0.014) and panic disorder (p:0.016). There was no significant difference between groups in terms of SDQ scores.Conclusions: These results suggest that RC, through its unique combination of physical exertion and mental focus, may offer protective benefits against certain anxiety disorders among adolescents. Further studies should be conducted to explore the potential use of RC as a preventive program for both healthy adolescents, as well as those with psychiatric disorder.